Exploring the role of antimicrobials in the selective growth of purple phototrophic bacteria through genome mining and agar spot assays. (8th August 2022) - Alloul, A.; Van Kampen, W.; Cerruti, M.; Wittouck, S.; Pabst, M.; Weissbrodt, D.G.
Abstract: Purple non‐sulphur bacteria (PNSB) are an emerging group of microbes attractive for applied microbiology applications such as wastewater treatment, plant biostimulants, microbial protein, polyhydroxyalkanoates and H2 production. These photoorganoheterotrophic microbes have the unique ability to grow selectively on organic carbon in anaerobic photobioreactors. This so‐called selectivity implies that the microbial community will have a low diversity and a high abundance of a particular PNSB species. Recently, it has been shown that certain PNSB strains can produce antimicrobials, yet it remains unclear whether these contribute to competitive inhibition. This research aimed to understand which type of antimicrobial PNSB produce and identify whether these compounds contribute to their selective growth. Mining 166 publicly‐available PNSB genomes using the computational tool BAGEL showed that 59% contained antimicrobial encoding regions, more specifically biosynthetic clusters of bacteriocins and non‐ribosomal peptide synthetases. Inter‐ and intra‐species inhibition was observed in agar spot assays for Rhodobacter blasticus EBR2 and Rhodopseudomonas palustris EBE1 with inhibition zones of, respectively, 5.1 and 1.5–5.7 mm. Peptidomic analysis detected a peptide fragment in the supernatant (SVLQLLR) that had a 100% percentage identity match with a known non‐ribosomal peptide synthetase with antimicrobial activity. Abstract : Significance and Impact of the Study: Purple non‐sulphur bacteria (PNSB) are attractive for applied microbiology and biotechnology because of their ability to grow selectively on organic carbon in photobioreactors. This capability has been attributed to traditional selection phenomena such as low oxygen levels, availability of organic acids and infrared light. In this study, a unique combination of genome mining tools and microbiological methods was used to explore whether antimicrobials contribute to selective growth. Our findings provide first insights into the antimicrobial biosynthesis potential of PNSB and provide ground for more advanced research on antimicrobial production by PNSB.